Ice-cream used as cryotherapy during high-dose melphalan conditioning reduces oral mucositis after autologous hematopoietic stem cell transplantation - Marcin Jasiński (Nature Portfolio, 2021)
Abstract Oral mucositis (OM) is one of the most frequent adverse events of high-dose conditioning chemotherapy with melphalan prior to autologous hematopoietic stem cell transplantation (AHSCT). It significantly reduces the patients’ quality of life. One of the preventive strategies for OM is cryotherapy. We retrospectively analyzed whether commercially available ice-cream could prevent OM during the melphalan infusion. We retrospectively analyzed 74 patients after AHSCT to see whether there is any correlation between OM and cryotherapy (ice-cream), melphalan dose (140 mg/m2 or 200 mg/m2). The incidence of OM in our study inversely correlated with cryotherapy in the form of ice-cream. Out of 74 patients receiving conditioning chemotherapy with high-dose melphalan, 52 received cryotherapy. Fifteen patients in the cryotherapy group (28.84%) developed OM, whereas 13 patients (59.09%) developed it in the group without cryotherapy. In a multiple linear regression test cryotherapy remained a significant protective factor against OM (p = 0.02) We have also seen the relationship between melphalan dose with OM (p < 0.005). Cryotherapy in the form of ice-cream is associated with a lower rate of OM and, therefore, could potentially be used as a cost-effective, less burdensome, and easy to implement method in prevention of oral mucositis.